(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Tributyltin chloride (TBTCl) tolerant marine bacterial isolates identified as Flavobacterium balustinum (strain S1), Vibrio harveyi (strain S2) Alcaligenes sp.2-6 (strain S3), Alacaligenes sp. swo (strain Sd) Sp from coastal Goa, were evaluated for resistance to antibiotics and some heavy metals. All the five TBTC resistant bacterial isolates were found to be resistant to most of the broad range of antibiotics used, such as Amikacin, Amozycillin, Ampicillin, Antimycin, Cephalothin, Chloramphenicol, Erythromycin, Gentamycin and Kanamycin. Strain S1 was resistant to most of the antibiotics used except for Kanamycin, Spectinomycin and Tetracycline. Strain S2 was sensitive to only Spectinomycin and resistant to all the antibiotics. Strain S3 and Sd showed similar pattern of resistance, both the isolates were resistant to most of the antibiotics used, except for Ciprofloxacin, Chloramphenicol, Rifampicin and Tetracycline. The cross tolerance to heavy metals was evaluated in terms of percent survival in presence of Hg 2+ Cd2+ As2O3. The LD50 values of isolates S1 and S2 was (2.0 mM), isolate Sd (1.5 mM), where as isolates S3 and Sp showed values of (1 mM) respectively for Cadmium. All the five isolates showed varied level of resistance to mercury, the isolates S3 and Sd showed low level of resistance i.e., with LD50 values of (1.5 mM and 1 mM), isolate S1 and S2 showed highest level of resistance to Hg2+ as LD50 values were (2.5 mM and 3 mM), the isolate Sp showed the lowest level of resistance to Hg2+ with LD50 value of (0.5 mM)., All five isolates grown in the presence of Arsenic oxide showed moderate level of resistance to Arsenic, isolate S1 S2 showed highest resistance to As2O3 with LD 50 value of (2.0 mM), isolates S3, Sd and Sp showed the highest level of resistance with LD 50 value of (2.5 mM) each respectively. The varied level of resistance of these five isolates to antibiotics and heavy metals may be plasmid borne and the resistance to antibiotics may be a result of drug inactivationmodification, target alteration and reduced accumulation owing to decreased permeability or increased efflux. However, in this case both the antibiotic and heavy metal resistance may be plasmid mediated